Levodopa Therapy for Parkinson's Disease: History, Current Status and Perspectives - Bogetofte, Helle; Alamyar, Arezo; Blaabjerg, Morten; Meyer, Morten (CNS & Neurological Disorders - Drug Targets, 2020)
Parkinson’s Disease (PD) is a neurodegenerative disorder characterized by a preferential degeneration of dopaminergic neurons in the substantia nigra pars compacta. This results in a profound decrease of striatal dopamine (DA) levels, which in turn leads to the cardinal motor symptoms of PD; muscle rigidity, hypo- and bradykinesia and resting tremor. Even 50 years after its initial use, the DA precursor levodopa (L-dopa), is still the most effective medical therapy for the symptomatic treatment of PD. Long-term L-dopa treatment is however, unfortunately associated with undesirable side effects such as motor fluctuations and dyskinesias. Furthermore, despite the disease alleviating effects of L-dopa, it is still discussed whether L-dopa has a neurotoxic or neuroprotective effect on dopaminergic neurons. Here we review the history of L-dopa, including its discovery, development and current use in the treatment of PD. We furthermore review current evidence of the L-dopa-induced side effects and perspectives of L-dopa treatment in PD compared to other established treatments such as DA-agonists and the inhibitors of catechol-o-methyltransferase and monoamine oxidase B.
Keywords: dyskinesia